Challenges and Strategies of Parental Engagement among Secondary School Learners in Sheema District, Uganda - Mugumya , Duncans; Mwesigye, Adrian R; Ahimbisibwe , Emmanuel Karoro (American Journal of Education and Practice, 2023)
Purpose: The study investigated challenges and strategies of parental engagement (PE) with respect to students' academic performance (SAP) in Sheema District, South Western Uganda. Methodology: The study employed qualitative approach using interpretative phenomenological approach of data collection, analysis, and interpretation. Participants of the study included purposively selected head teachers, deputy head teachers, directors of studies, chairpersons and treasurers of both Parents Teachers Associations (PTA) and Boards of Governors (BOG) of ten government grant-aided USE schools (GGAUSES) in the District. Using thematic analysis, various themes and sub-themes of PE issues and methods were derived from qualitative data. Findings: The challenges of parental engagement in learners' academic activities in government grant-aided USE schools in Sheema District generated three themes: Home environment-related challenges (HERC), school environment-related challenges (SERC), and government-related challenges (GRC). Each of these generated several subthemes. The strategies for overcoming the parental engagement challenges included social and economic tactics, leadership and management strategies as well as legislation and regulation. Recommendation: The study recommend a deliberate move on the part of key stakeholders to enhance parental engagement through abating its challenges be emphasised and that will foster learners' academic performance.